An examination of college student athletes' academic achievement - Hildenbrand, Kasandra J. (Kansas State University, 2005)
There is growing concern over the academic performance of student athletes in today’s institutions of higher education. Across all media, the public is constantly reminded that the success rate of student athletes is not what it should be. One hypothesis for this poor performance is that athletes are not as well prepared to go to college as their non-athletic counterparts. This could be attributed to low high school academic standards, or high school teachers allowing athletes to underperform due to their status as an athlete, or a lack of time for studying due to sport participation. The NCAA mandates certain academic standards for entrance into college, yet athletes still struggle to maintain passing grades, with some failing to graduate. Most college students are admitted to college based on their potential to benefit from an institution’s programs and educational opportunities. In many institutions, especially at the Division I level, student athletes are admitted for their potential to provide benefits for the institutions. This study compared the college graduating GPA of athletes and nonathletes relative to ACT score to determine if athletes were underperforming in college. Additionally the effect of gender, ethnicity and type of sport was examined. This study used hierarchical regression equations to examine these effects. When looking at athletes only, type of sport, gender, and ethnicity had very little influence on graduating GPA. When examining all students, ACT test scores were significantly related to college graduating GPA.
Keywords: College student athletes; Academic achievement; Academic preparedness; Gender and ethnicity; Education, Guidance and Counseling (0519)